The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1440-1827.1993.tb02919.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the gall‐bladder arising in adenomyomatosis

Abstract: We describe a case of well differentiated adenocarcinoma of the gall-bladder that arose from a localized type of adenomyomatosis. Grossly, the cancer was located in the fundus and exhibited a polypoid and well demarcated nodule with multiple small cysts. Histologically, the nodule consisted of glandular structures and stroma containing bundles of smooth muscle cells. The glandular epithelia were varied in appearance, ranging from malignant to benign glands. The adenocarcinoma was limited to the nodule, with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…However, in their case, the distribution of the ADM was not truly localized and the cancer seemed to arise from overlying mucosa rather within the ADM. Katoh et al 18 also described a similar case in which the mucosa adjacent to the ADM was hyperplastic and noninvasive adenocarcinoma appeared to originate from the overlying gallbladder mucosa. The third case described by Kurihara et al 19 had a distinct nodule that showed ADM as well as intermingled malignant cells as seen in our case; however, in their case they also saw microcalculi in the fibrous stroma as well as the atypical glands of ADM. We conclude that the origin of malignant foci in their case possibly resulted from chronic irritation due to microcalculi.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, in their case, the distribution of the ADM was not truly localized and the cancer seemed to arise from overlying mucosa rather within the ADM. Katoh et al 18 also described a similar case in which the mucosa adjacent to the ADM was hyperplastic and noninvasive adenocarcinoma appeared to originate from the overlying gallbladder mucosa. The third case described by Kurihara et al 19 had a distinct nodule that showed ADM as well as intermingled malignant cells as seen in our case; however, in their case they also saw microcalculi in the fibrous stroma as well as the atypical glands of ADM. We conclude that the origin of malignant foci in their case possibly resulted from chronic irritation due to microcalculi.…”
Section: Discussionsupporting
confidence: 47%
“…The epithelial metaplasia was present in all 60 specimens and was more striking in the fundal compartment (P = .003). These studies and other sporadic case reports suggest that the long-standing biliary stasis and resultant mucosal changes in the fundal compartment may explain the high prevalence of gallbladder cancer in elderly patients with segmental-type ADM. 4,7,16,17 The sporadic occurrence of gallbladder cancer has been reported with localized-type ADM. 8,18,19 In the case described by Aldridge et al, 8 the distribution of ADM grossly as well as microscopically was within the wall of the gallbladder. However, in their case, the distribution of the ADM was not truly localized and the cancer seemed to arise from overlying mucosa rather within the ADM. Katoh et al 18 also described a similar case in which the mucosa adjacent to the ADM was hyperplastic and noninvasive adenocarcinoma appeared to originate from the overlying gallbladder mucosa.…”
Section: Discussionmentioning
confidence: 93%
“…However, in the present study, EUS showed multiple microcysts in one case with adenocarcinoma because of coexistent proliferated Rokitansky-Aschoff sinuses. Although adenomyomatosis has been considered to have no malignant potential, several cases of gallbladder cancers concomitant with adenomyomatosis (or proliferated Rokitansky-Aschoff sinus) have been reported (17)(18)(19)(20)(21)(22). Therefore, we should be aware that multiple microcysts can be also seen in neoplastic polyps when they contain concomitant proliferated Rokitansky-Aschoff sinus.…”
Section: Discussionmentioning
confidence: 88%
“…So far, it is not known whether adenomyomatosis has any clinical significance and whether it will truly lead to inflammation or even cancer (Chan-Wilde et al 1990). Based on the observation of dysplastic changes and the association of gallbladder carcinoma with adenomyomatosis, it has been suggested that adenomyomatosis might represent a premalignant condition (Bevan 1970;Aldridge et al 1991;Funabiki et al 1993;Kurihara et al 1993;Imai et al 2011). Diffuse adenomyomatosis was found to be associated with dysplastic gallbladder adenoma (Di Carlo et al 2010).…”
Section: Is Adenomyomatosis a Precancerous Lesion?mentioning
confidence: 99%